Negative electrode, method for manufacturing the same and secondary battery comprising the same
By employing a styrene butadiene rubber primer layer and polyacrylic acid-based binder composition, the silicon-based cathode's expansion and contraction issues are mitigated, enhancing the battery's lifespan and capacity retention.
Patent Information
- Application Number
- KR1020220008082
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-19
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Silicon-based negative electrode materials in lithium-ion batteries experience significant volume expansion and contraction during charging and discharging, leading to reduced adhesion and conductivity, which compromises the lifespan of the battery.
A manufacturing method involving a primer layer of styrene butadiene rubber and a composite layer with a polyacrylic acid-based binder is applied to the silicon-based cathode, optimizing the ratio of butadiene-derived and acrylic acid-derived structural units to enhance adhesion and flexibility, thereby mitigating expansion and contraction.
The method significantly improves the lifespan characteristics of the secondary battery by maintaining electrode flexibility and adhesion, resulting in enhanced capacity retention rates and reduced expansion rates.
Smart Images

Figure 112022007087549-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a negative electrode, a method for manufacturing the same, and a secondary battery including the same. Background Technology
[0002] Lithium secondary batteries, which have recently been gaining attention as power sources for small portable electronic devices, are batteries that exhibit high energy density by using an organic electrolyte and showing a discharge voltage more than twice as high as that of conventional batteries using an alkaline aqueous solution.
[0003] As science and technology advance and various devices are developed, high energy density is becoming important in addition to miniaturization and weight reduction of lithium-ion batteries to meet the miniaturization and high performance requirements of various devices. In other words, high-capacity lithium-ion batteries are required.
[0004] Although graphite is mainly used as a negative electrode material for lithium secondary batteries, graphite has a low capacity of 372 mAh / g per unit mass, making it difficult to increase the capacity of lithium secondary batteries.
[0005] Much research is being conducted to apply anode active materials, such as silicon, which exhibit higher capacity than graphite. However, compared to graphite, silicon as an anode active material has a problem in that it exhibits significant volume expansion during lithium insertion and extraction, which leads to reduced adhesion and conductivity within the electrode, resulting in inferior lifespan characteristics. The problem to be solved
[0006] The present invention aims to solve the above-mentioned problems by mitigating the expansion and contraction of a silicon-based negative electrode active material during charging and discharging and providing flexibility to the electrode, thereby providing a negative electrode with improved lifespan characteristics, a method for manufacturing the same, and a secondary battery including the said negative electrode. means of solving the problem
[0007] According to one aspect of the present invention, a method for manufacturing a cathode is provided, comprising the steps of: applying a first slurry containing styrene butadiene rubber on at least one surface of a cathode current collector; applying a second slurry containing a cathode active material and a polyacrylic acid-based binder on the first slurry; and drying and rolling the cathode current collector coated with the first slurry and the second slurry, wherein the cathode active material comprises a silicon-based cathode active material.
[0008] The above polyacrylic acid-based binder may contain 40 to 90 mole% of acrylic acid-derived structural units relative to the total moles of binder.
[0009] The above styrene butadiene rubber may contain 10 to 95 mole% of butadiene-derived structural units relative to the total moles of styrene butadiene rubber.
[0010] The above polyacrylic acid-based binder may include an acrylic acid-derived structural unit; and one or more selected from the group consisting of a vinyl alcohol-derived structural unit, an acrylamide-derived structural unit, an acrylate-derived structural unit, and a vinyl acetate-derived structural unit.
[0011] The content of butadiene-derived structural units present in the styrene butadiene rubber and the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder can satisfy the relationship of Equation 1 below.
[0012] [Equation 1]
[0013]
[0014] The step of applying the second slurry can be performed before the first slurry is dried.
[0015] According to another aspect of the present invention, a cathode is provided comprising: a negative current collector; a primer layer formed on at least one surface of the negative current collector and comprising styrene butadiene rubber; and a negative composite layer formed on the primer layer and comprising a negative active material and a polyacrylic acid-based binder, wherein the negative active material comprises a silicon-based negative active material.
[0016] The above polyacrylic acid-based binder may contain 40 to 90 mole% of acrylic acid-derived structural units relative to the total moles of binder.
[0017] The above styrene butadiene rubber may contain 10 to 95 mole% of butadiene-derived structural units relative to the total moles of styrene butadiene rubber.
[0018] The above polyacrylic acid-based binder may include one or more selected from the group consisting of acrylic acid-derived structural units; vinyl alcohol-derived structural units, acrylamide-derived structural units, acrylate-derived structural units, and vinyl acetate-derived structural units.
[0019] The content of butadiene-derived structural units present in the styrene butadiene rubber and the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder can satisfy the relationship of Equation 1 below.
[0020] [Equation 1]
[0021]
[0022] The loading amount of the primer layer may be 0.1 to 2 weight percent of the total loading amount of the cathode.
[0023] According to another aspect of the present invention, a secondary battery is provided comprising: a cathode; an anode; and a separator interposed between the anode and the cathode. Effects of the invention
[0024] According to the present invention, the expansion and contraction of the silicon-based negative electrode active material during charging and discharging are mitigated, and the flexibility of the electrode is improved, so that, as a result, the lifespan characteristics of the secondary battery can be significantly improved. Brief explanation of the drawing
[0025] FIG. 1 schematically shows a cathode according to one embodiment of the present invention. Specific details for implementing the invention
[0026] Preferred embodiments of the present invention will be described below with reference to various examples. However, embodiments of the present invention may be modified in various other forms, and the scope of the present invention is not limited to the embodiments described below.
[0027] The present invention relates to a negative electrode, a method for manufacturing the same, and a secondary battery including the same.
[0028] According to one aspect of the present invention, a method for manufacturing a cathode is provided, comprising the steps of: applying a first slurry containing styrene butadiene rubber on at least one surface of a cathode current collector; applying a second slurry containing a cathode active material and a polyacrylic acid-based binder on the first slurry; and drying and rolling the cathode current collector coated with the first slurry and the second slurry, wherein the cathode active material comprises a silicon-based cathode active material.
[0029] First, a step of applying a first slurry containing styrene butadiene rubber on at least one surface of a negative electrode current collector may be performed. In the present invention, the first slurry forms a primer layer on the negative electrode current collector, and the first slurry may contain styrene butadiene rubber. By forming a primer layer containing a large amount of styrene butadiene rubber on the surface of the electrode in this way, flexibility can be imparted to the electrode, and accordingly, the lifespan characteristics of the secondary battery can be improved.
[0030] The above styrene butadiene rubber may contain 10 to 95 mole% of butadiene-derived structural units relative to the total moles of styrene butadiene rubber, and it is preferable to contain 30 to 90 mole%. If the content of butadiene-derived structural units is less than 10 mole%, there is a problem with the low adhesive strength of the styrene butadiene rubber itself, whereas if it exceeds 95 mole%, the resistance of the electrode becomes too high, which may reduce the effectiveness of the invention.
[0031] The first slurry may contain a solvent, and while not specifically limited, N-methylpyrrolidone (NMP), acetone, water, etc. may be used as the solvent. Meanwhile, if necessary, one or more binders selected from the group consisting of carboxymethylcellulose (CMC), polyvinylpyridine (PVP), and polyacrylic acid (PAA)-based binders may be added to control the viscosity of the first slurry, and the binder may be included in an amount of 5% by weight or less relative to the total weight of the first slurry.
[0032] Meanwhile, the negative electrode current collector to which the first slurry is applied is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, similar to the positive electrode current collector, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative electrode active material, and it may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.
[0033] Next, a step of applying a second slurry comprising a negative electrode active material and a polyacrylic acid-based binder onto the first slurry is performed, and the second slurry can form a negative electrode composite layer.
[0034] The above-mentioned negative electrode active material may be a silicon-based negative electrode active material. Although not specifically limited, the silicon-based negative electrode active material may use at least one selected from the group consisting of SiOx (0<2) particles, Si-C composites, and Si-Y alloys (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, rare earth elements, and combinations thereof), and for example, it may be SiO.
[0035] In the present invention, the binder included in the second slurry may be a polyacrylic acid-based binder. More specifically, the binder may include an acrylic acid-derived structural unit and may also include one or more selected from the group consisting of a vinyl alcohol-derived structural unit, an acrylamide-derived structural unit, an acrylate-derived structural unit, and a vinyl acetate-derived structural unit. Additionally, each structural unit present in the polyacrylic acid-based binder may form cross-linking with one another.
[0036] Water-based binders such as polyacrylic acid have rigid characteristics characteristic of polymers, but at the same time, they also have blittle characteristics. Therefore, electrodes fabricated using polyacrylic acid alone as a binder are highly likely to experience problems such as breakage during bending, detachment during notching, processability issues in the electrode state, and cracking during charging and discharging processes even after being fabricated into a battery. In the present invention, by using a polyacrylic acid-based binder comprising an acrylic acid-derived structural unit; and one or more selected from the group consisting of a vinyl alcohol-derived structural unit, an acrylamide-derived structural unit, an acrylate-derived structural unit, and a vinyl acetate-derived structural unit, the above disadvantages of water-based binders can be improved, and at the same time, the expansion of the silicon-based negative electrode active material can be suppressed. Preferably, a polyacrylic acid-polyvinyl alcohol copolymer comprising an acrylic acid-derived structural unit and a vinyl alcohol-derived structural unit can be used.
[0037] The above polyacrylic acid-based binder may contain 40 to 90 mol% of acrylic acid-derived structural units with respect to the total moles of the binder, and it is preferable to contain 40 to 80 mol%. If the content of acrylic acid-derived structural units is less than 40 mol%, the effect of inhibiting the expansion of the silicon-based negative electrode active material may be insufficient, whereas if the content of acrylic acid-derived structural units exceeds 90 mol%, it is difficult to improve cracks in the electrode layer.
[0038] Meanwhile, it is preferable that the content of butadiene-derived structural units present in the styrene butadiene rubber be determined by considering the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder of the second slurry. As the content of acrylic acid-derived structural units increases, the expansion inhibition power increases, but the adhesion power decreases, and the possibility of cracking may increase. Accordingly, when the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder of the second slurry is high, the stability of the electrode can be significantly improved by imparting adhesion power and flexibility by using styrene butadiene rubber with a high content of butadiene-derived structural units in the first slurry as well. Preferably, the content of butadiene-derived structural units and the content of acrylic acid-derived structural units can satisfy the relationship of Equation 1 below.
[0039] [Equation 1]
[0040]
[0041] In addition, it is preferable that the step of applying the second slurry be performed before the first slurry dries. If the first slurry dries and becomes a polymer, it does not mix with the second slurry coated thereon, and an electrode is produced with a boundary between the first slurry layer and the second slurry layer, and a problem may arise where the adhesion strength at this boundary is very low. Accordingly, if the second slurry is applied before the first slurry dries, some of the styrene butadiene rubber contained in the first slurry moves upward due to a migration phenomenon during the drying process (styrene butadiene rubber particles move in the direction of evaporation as water evaporates because their specific gravity is close to 1), naturally mixes with the second slurry, and can impart high electrode adhesion strength and partially offset the brittleness of the polyacrylic acid-based binder.
[0042] If necessary, the second slurry may additionally include a conductive material. The conductive material is not particularly limited as long as it is conductive without causing chemical changes in the lithium secondary battery, and for example, carbon black such as carbon black, acetylene black, Ketjen black, channel black, Farness black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as aluminum or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used.
[0043] A cathode can be manufactured by drying and rolling a cathode current collector coated with the first slurry and the second slurry. Meanwhile, the coating and drying of the slurry can be performed using methods generally practiced in the industry and are not particularly limited. For example, coating may be performed using a slot die coating method, and may also use Meyer bar coating, gravure coating, immersion coating, spray coating, etc., and drying may be performed, for example, in a drying atmosphere at room temperature. The cathode composite layer formed on the cathode current collector by coating and drying can be passed through a metal rolling roll of a calendering equipment to perform rolling.
[0044] According to another aspect of the present invention, a cathode manufactured by the method described above is provided. FIG. 1 schematically illustrates a cathode according to one embodiment of the present invention. According to the present invention, a cathode (100) is provided comprising: a cathode current collector (10); a primer layer (20) formed on at least one surface of the cathode current collector (10) and comprising styrene butadiene rubber; and a cathode composite layer (30) formed on the primer layer (20) and comprising a cathode active material and a polyacrylic acid-based binder, wherein the cathode active material comprises a silicon-based cathode active material.
[0045] As described above, the first slurry containing styrene butadiene rubber forms a primer layer (20), and the second slurry applied on the first slurry forms a cathode composite layer (30). Since the composition and content of each layer have been described above, further explanation is omitted here.
[0046] Meanwhile, the loading amount of the primer layer (20) may be 0.1 to 2 weight percent of the total loading amount of the cathode (100). If the loading amount is less than 0.1 weight percent, the styrene butadiene rubber content is insufficient, making it difficult to secure electrode flexibility, and if the loading amount exceeds 2 weight percent, the styrene butadiene content becomes excessively high, which may increase the resistance of the electrode.
[0047] According to another aspect of the present invention, a secondary battery is provided comprising: a cathode; an anode; and a separator interposed between the anode and the cathode.
[0048] The anode may include all anodes commonly used in the industry. For example, the anode may be manufactured by applying a mixture of an anode active material, a conductive material, and a binder onto an anode current collector and then drying it. The anode current collector may be made of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc. The current collector may also form fine irregularities on its surface to increase the adhesion of the anode active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible.
[0049] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium transition metal composite oxide comprising lithium and at least one transition metal comprising nickel, cobalt, manganese, and aluminum, preferably a lithium transition metal composite oxide comprising lithium and a transition metal comprising nickel, cobalt, and manganese.
[0050] The anode composite layer may additionally include a binder, and the binder is a component that assists in the binding of active materials and conductive materials, and in binding to the current collector. Specifically, such annode binders may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene ter polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, and fluororubber, preferably polyvinylidene fluoride.
[0051] The above anode composite layer may additionally include one or more conductive materials selected from the group consisting of graphite, carbon black, metal powder, and conductive oxide to improve conductivity.
[0052] In addition, the separator may be a conventional porous polymer film that has been used as a separator in the past, such as a porous polymer film made of a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, used alone or in a laminate thereof, or a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber, polyethylene terephthalate fiber, etc., may be used, but is not limited thereto.
[0053] The secondary battery manufactured according to the present invention can significantly improve the lifespan characteristics of the secondary battery by mitigating the expansion and contraction of the silicon-based negative electrode active material during charging and discharging and improving the flexibility of the electrode.
[0054] A secondary battery module can be configured using a secondary battery according to the present invention as a unit cell, and furthermore, one or more of the modules can be packaged within a pack case to form a secondary battery pack. The secondary battery module and the secondary battery pack including the above-described secondary battery module can be applied to various devices. Such devices may be applied to means of transportation such as electric bicycles, electric vehicles, and hybrid vehicles, but the present invention is not limited thereto and can be applied to various devices capable of using the secondary battery module and the secondary battery pack including the same, and this also falls within the scope of the rights of the present invention.
[0055] The present invention will be explained in more detail below through specific embodiments. The following embodiments are merely examples to aid in understanding the present invention and do not limit the scope of the present invention.
[0056] Examples
[0057] Manufacturing of the cathode
[0058] Example 1
[0059] A first slurry was prepared by adding distilled water to styrene butadiene rubber containing 10 mol% of butadiene-derived structural units and diluting it to 10 wt%.
[0060] A second slurry was prepared by adding and mixing a polyacrylic acid-polyvinyl alcohol copolymer containing SiOx and graphite as cathode active materials, carbon nanotubes (CNT) as conductive materials, and 40 mol% of acrylic acid-derived structural units as binders into distilled water, which is a solvent.
[0061] A first slurry was applied to a copper foil with a thickness of 10 μm, and before drying the first slurry, a second slurry was applied to the first slurry, and then dried and rolled to manufacture a cathode.
[0062] Example 2
[0063] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 30 mol% of butadiene-derived structural units was used.
[0064] Example 3
[0065] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 90 mol% of butadiene-derived structural units was used.
[0066] Example 4
[0067] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 30 mol% of butadiene-derived structural units and a polyacrylic acid-polyvinyl alcohol copolymer containing 80 mol% of acrylic acid-derived structural units were used.
[0068] Example 5
[0069] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 60 mol% of butadiene-derived structural units and a polyacrylic acid-polyvinyl alcohol copolymer containing 80 mol% of acrylic acid-derived structural units were used.
[0070] Example 6
[0071] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 90 mol% of butadiene-derived structural units and a polyacrylic acid-polyvinyl alcohol copolymer containing 80 mol% of acrylic acid-derived structural units were used.
[0072] Example 7
[0073] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 5 mol% of butadiene-derived structural units was used.
[0074] Example 8
[0075] A cathode was prepared in the same manner as in Example 1, except that styrene butadiene rubber containing 98 mol% of butadiene-derived structural units was used.
[0076] Example 9
[0077] A cathode was prepared in the same manner as in Example 1, except that a polyacrylic acid-polyvinyl alcohol copolymer containing 5 mol% of acrylic acid-derived structural units was used.
[0078] Example 10
[0079] A cathode was prepared in the same manner as in Example 1, except that a polyacrylic acid-polyvinyl alcohol copolymer containing 95 mol% of acrylic acid-derived structural units was used.
[0080] Comparative Example 1
[0081] A cathode slurry was prepared by adding SiOx as the cathode active material, carboxymethylcellulose (CMC) as the binder, and styrene butadiene rubber to distilled water as the solvent.
[0082] A cathode was manufactured by applying the above cathode slurry to a copper foil with a thickness of 10 μm, followed by drying and rolling.
[0083] Comparative Example 2
[0084] A first slurry was prepared by adding distilled water to styrene butadiene rubber containing 90 mol% of butadiene-derived structural units and diluting it to 10 wt%.
[0085] A second slurry was prepared by adding SiOx and graphite as cathode active materials, carbon nanotubes (CNT) as conductive materials, carboxymethylcellulose (CMC) and styrene butadiene rubber as binders to distilled water as a solvent.
[0086] A first slurry was applied to a copper foil with a thickness of 10 μm, and before drying the first slurry, a second slurry was applied to the first slurry, and then dried and rolled to manufacture a cathode.
[0087] Comparative Example 3
[0088] A negative electrode slurry was prepared by adding and mixing SiOx and graphite as negative electrode active materials, carbon nanotubes (CNT) as conductive materials, and a polyacrylic acid-polyvinyl alcohol copolymer containing 40 mol% of acrylic acid-derived structural units to distilled water as a solvent.
[0089] A cathode was manufactured by applying the above cathode slurry to a copper foil with a thickness of 10 μm, followed by drying and rolling.
[0090] Comparative Example 4
[0091] A cathode slurry was prepared by adding and mixing SiOx and graphite as cathode active materials, carbon nanotubes (CNT) as conductive materials, a polyacrylic acid-polyvinyl alcohol copolymer containing 40 mol% of acrylic acid-derived structural units and styrene butadiene rubber containing 90 mol% of butadiene-derived structural units as binders into distilled water as a solvent.
[0092] A cathode was manufactured by applying the above cathode slurry to a copper foil with a thickness of 10 μm, followed by drying and rolling.
[0093] manufacturing of secondary batteries
[0094] An anode slurry was prepared by adding 50 parts by weight of a solid mixture of a ternary active material (Li(Ni0.5Mn0.3Co0.2)O2) as the anode active material, carbon black as the conductive material, and polyvinylidene fluoride (PVDF) as the binder in a ratio of 90:5:5 (wt%) to N-methyl-2-pyrrolidone, which is the solvent, and then applying the anode slurry to an aluminum foil with a thickness of 12 μm, drying, and rolling to produce an anode.
[0095] An electrode assembly was prepared by laminating the cathode and anode prepared according to Examples 1 to 10 and Comparative Examples 1 to 4 together with a polyethylene porous film, then placing the assembly into a pouch-type battery case, injecting a non-aqueous electrolyte into each, and sealing it to produce a lithium secondary battery.
[0096] Evaluation of cathode expansion rate and capacity retention rate
[0097] The negative electrode expansion rate and capacity retention rate were measured for the secondary battery manufactured according to the above. The negative electrode expansion rate was measured according to Equation 2 below, and the capacity retention rate was measured according to Equation 3 below. The results are shown in Table 1 below.
[0098] [Equation 2]
[0099] Cathode Expansion Rate (%) = [(Cathode thickness in full charge state after 3 charge / discharge cycles - Initial cathode thickness) / (Initial cathode thickness)] X 100
[0100] [Equation 3]
[0101] Capacity Retention Rate (%) = (Discharge Capacity after 300 cycles / Discharge Capacity per cycle) X 100
[0102] Content of acrylic acid-derived structural units (mol%) Content of butadiene-derived structural units (mol%) Primer layer Cathode expansion rate (%) Dose retention rate (%) Comparative Example 1 - - X 33.2 76.5 Comparative Example 2 - 90 O 33.0 77.2 Comparative Example 3 40 - X 29.6 79.0 Comparative Example 4 40 90 X 30.8 84.1 Example 1 40 10 O 30.7 90.6 Example 2 40 30 O 30.5 93.4 Example 3 40 90 O 30.2 93.6 Example 4 80 30 O 30.2 90.8 Example 5 80 60 O 30.1 93.5 Example 6 80 90 O 29.9 93.9 Example 7 40 5 O 30.8 85.3 Example 8 40 98 O 30.0 89.2 Example 9 5 10 O 32.5 78.1 Example 10 95 10 O 29.2 72.6
[0103] Referring to Table 1 above, Comparative Example 1, which lacks a primer layer containing styrene butadiene rubber and uses carboxymethylcellulose (CMC) and styrene butadiene rubber as binders, was found to have the lowest cathodic expansion rate and capacity retention rate. In Comparative Example 2, although the cycle life was slightly improved due to the effect of mitigating migration and improving resistance of styrene butadiene rubber by the styrene butadiene rubber-containing primer layer, it was confirmed that both the cathodic expansion rate and capacity retention rate were inferior.
[0104] Comparative Example 3, which used a polyacrylic acid-based binder without a styrene butadiene rubber-containing primer layer, showed improved electrode expansion rate, but it was confirmed that the effect of improving lifespan characteristics was not significant due to cracking caused by the lack of flexibility of the electrode.
[0105] Comparative Example 4, which includes a polyacrylic acid-based binder and styrene butadiene rubber in a single-layer structure, shows some improvement in flexibility but does not show a significant improvement in lifespan characteristics, and due to the swelling characteristics of the styrene butadiene rubber itself, the electrode expansion rate increased slightly compared to Comparative Example 3.
[0106] Examples 1 to 10 represent a cathode according to the present invention. By comparing Examples 1 to 6 with Examples 7 to 10, electrode performance can be confirmed based on the content of acrylic acid-derived structural units and butadiene-derived structural units. When the content of acrylic acid-derived structural units satisfies 40 to 90 mol% and the content of butadiene-derived structural units satisfies 40 to 90 mol%, the cathode expansion rate of the cathode active material is significantly improved, and the capacity retention rate of the battery is also found to be very high.
[0107] Meanwhile, when comparing Examples 1 to 3 with Examples 4 to 6, it was found that when the content of acrylic acid-derived structural units increases, it is desirable for the content of butadiene-derived structural units to increase, and in particular, when the content of acrylic acid-derived structural units and the content of acrylic acid-derived structural units satisfy the relationship of Formula 1 below, the cathodic expansion rate and capacity retention rate are further improved.
[0108] [Equation 1]
[0109]
[0110] Although embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and it will be obvious to those skilled in the art that various modifications and variations are possible within the scope of the technical concept of the present invention as described in the claims. Explanation of the symbols
[0111] 10: Cathode current collector 20: Primer layer 30: Cathode composite layer 100: Cathode
Claims
Claim 1 A method for manufacturing a cathode comprising: a step of applying a first slurry containing styrene butadiene rubber onto at least one surface of a cathode current collector; a step of applying a second slurry containing a cathode active material and a polyacrylic acid-based binder onto the first slurry; and a step of drying and rolling the cathode current collector coated with the first slurry and the second slurry, wherein the cathode active material comprises a silicon-based cathode active material and the polyacrylic acid-based binder comprises 40 to 90 mol% of acrylic acid-derived structural units based on the total molar amount of binder. Claim 2 delete Claim 3 A method for manufacturing a cathode according to claim 1, wherein the styrene butadiene rubber comprises 10 to 95 mol% of butadiene-derived structural units based on the total molar amount of styrene butadiene rubber. Claim 4 A method for manufacturing a cathode according to claim 1, wherein the polyacrylic acid-based binder comprises an acrylic acid-derived structural unit; and one or more selected from the group consisting of a vinyl alcohol-derived structural unit, an acrylamide-derived structural unit, an acrylate-derived structural unit, and a vinyl acetate-derived structural unit. Claim 5 A method for manufacturing a cathode according to claim 1, wherein the content of butadiene-derived structural units present in the styrene-butadiene rubber and the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder satisfy the relationship of Equation 1 below. [Equation 1] Claim 6 A method for manufacturing a cathode according to claim 1, wherein the step of applying the second slurry is performed before the first slurry is dried. Claim 7 A cathode comprising: a negative current collector; a primer layer formed on at least one surface of the negative current collector and comprising styrene butadiene rubber; and a negative composite layer formed on the primer layer and comprising a negative active material and a polyacrylic acid-based binder, wherein the negative active material comprises a silicon-based negative active material and the polyacrylic acid-based binder comprises 40 to 90 mol% of acrylic acid-derived structural units based on the total moles of binders. Claim 8 delete Claim 9 In claim 7, the styrene butadiene rubber is a cathode comprising 10 to 95 mol% of butadiene-derived structural units with respect to the total molar amount of styrene butadiene rubber. Claim 10 In claim 7, the polyacrylic acid-based binder comprises an acrylic acid-derived structural unit; and a cathode comprising one or more selected from the group consisting of a vinyl alcohol-derived structural unit, an acrylamide-derived structural unit, an acrylate-derived structural unit, and a vinyl acetate-derived structural unit. Claim 11 In claim 7, the content of butadiene-derived structural units present in the styrene-butadiene rubber and the content of acrylic acid-derived structural units present in the polyacrylic acid-based binder satisfy the relationship of Equation 1 below. [Equation 1] Claim 12 In claim 7, the loading amount of the primer layer is 0.1 to 2 weight percent of the total loading amount of the cathode. Claim 13 A secondary battery comprising a negative electrode according to any one of claims 7 and 9 to 12; a positive electrode; and a separator interposed between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Negative electrode for rechargeable lithium battery, and rechargeable lithium battery including same
KR1020190134021A
